Singapore-Malaysia relations under Abdullah Badawi - Saw, Swee-Hock 1931- (Institute of Southeast Asian Studies, 2006)
A project of the ISEAS Malaysia Study Programme, this book documents the series of important events that have contributed to the warmer relations enjoyed by Singapore and Malaysia under Abdullah Badawi. It covers such topics as solving bilateral ties, intensifying official visits, developing people-to-people contacts, and more.